Ini Aku, Utuslah Aku (Suatu Kajian Teologi Sistematika Esensi Panggilan Pendeta Sebagai Hamba Tuhan) - Pintor Marihot Sitanggang; Maruli Robintang Munthe (Jurnal Teologi Cultivation, 2023)
This article describes the essense of pastor’s calling as the servant of God, surrendered and offered their life to be sending and calling of God to serve people of God. In theological perspective, words “here I am, send me” as proclamation of total surrendering a servant of God to God, to serve Him in life without hesitation. The aim of this article reminds the pastors always remembering and living their calling as the servant of God. The calling as the Servant of God always reminding the Pastors of their duty and responsibility in the Church eventhough challenges has to be faced in their life.  This article used the qualitative (library) research method. Start with biblical study, then what the teologians said about it, and how the contextualization in the journey of Church ministry in this present time.